Impact of Guideline‐Discordant Treatment on Cost and Health Care Utilization in Older Adults with Early‐Stage Breast Cancer. (17th August 2018) - Williams, Courtney P.; Kenzik, Kelly M.; Azuero, Andres; Williams, Grant R.; Pisu, Maria; Halilova, Karina I.; Ingram, Stacey A.; Yagnik, Supriya K.; Forero, Andres; Bhatia, Smita; Rocque, Gabrielle B.
Abstract: Background: National Comprehensive Cancer Network (NCCN) guideline‐based treatment is a marker of high‐quality care. The impact of guideline discordance on cost and health care utilization is unclear. Materials and Methods: This retrospective cohort study of Medicare claims data from 2012 to 2015 included women age ≥65 with stage I–III breast cancer receiving care within the University of Alabama at Birmingham Cancer Community Network. Concordance with NCCN guidelines was assessed for treatment regimens. Costs to Medicare and health care utilization were identified from start of cancer treatment until death or available follow‐up. Adjusted monthly cost and utilization rates were estimated using linear mixed effect and generalized linear models. Results: Of 1, 177 patients, 16% received guideline‐discordant treatment, which was associated with nonwhite race, estrogen receptor/progesterone receptor negative, human epidermal growth receptor 2 (HER2) positive, and later‐stage cancer. Discordant therapy was primarily related to reduced‐intensity treatments (single‐agent chemotherapy, HER2‐targeted therapy without chemotherapy, bevacizumab without chemotherapy, platinum combinations without anthracyclines). In adjusted models, average monthly costs for guideline‐discordant patients were 936 higher compared with concordant (95% confidence limits 611, 1, 260). For guideline‐discordant patients, adjusted rates of emergency department visits and hospitalizations per thousand observations were 25% higher (49.9 vs. 39.9) and 19% higher (24.0 vs. 20.1) per month than concordant patients, respectively. Conclusion: One in six patients with early‐stage breast cancer received guideline‐discordant care, predominantly related to undertreatment, which was associated with higher costs and rates of health care utilization. Additional randomized trials are needed to test lower‐toxicity regimens and guide clinicians in treatment for older breast cancer patients. Implications for Practice: Previous studies lack details about types of deviations from chemotherapy guidelines that occur in older early‐stage breast cancer patients. Understanding the patterns of guideline discordance and its impact on patient outcomes will be particularly important for these patients. This study found 16% received guideline‐discordant care, predominantly related to reduced intensity treatment and associated with higher costs and rates of health care utilization. Increasing older adult participation in clinical trials should be a priority in order to fill the knowledge gap about how to treat older, less fit patients with breast cancer. Abstract : This article evaluates concordance of treatment regimens received (hormone therapy, chemotherapy, and targeted therapies) with NCCN guidelines for older women with early stage breast cancer, focusing on understanding the categories of discordant treatments and the impact of discordance on health care utilization and spending.